PENGELOLAAN LAHAN DENGAN SISTEM AGROFORESTRY OLEH MASYARAKAT BADUY DI BANTEN SELATAN - Gunggung Senoaji (Environmental Research Center (PPLH) of Udayana University, 2012)
Land management with agroforestry systems have proven economic benefits for communities and benefit protection for the environment. Baduy community in South Banten has implemented agroforestry systems in managing the farm. This study aims to determine the process of agricultural land management with agroforestry systems by Baduy community. The method used is survey method with the partisipatory approaches. Data retrieval is done by field observations and in-depth open interviews. The results showed that Baduy community, especially Baduy-Luar, implement agroforestry systems “kebun sengon campuran” in managing the farm. The farming systems is dryland rice with shifting cultivation with 5-7 years of fallow period. The procedure for farming is governed by customary norms that must be obeyed by the whole community Baduy. On the farm planted with agricultural crops and trees. In the first year of land, found rice vegetables, pulses, the chicks sengon, and trees. In the second years of land found various pulses, vegetables, and tree sengon, and the third-fifth year land has formed the mix sengon plantations. The age of stands sengon as the fallow period in management of their land.